2007
DOI: 10.1021/es0716913
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent Broadband Cavity-Enhanced Absorption Spectroscopy in the near-Ultraviolet: Application to HONO and NO2

Abstract: The first application of incoherent broadband cavity-enhanced absorption spectroscopy (IBBCEAS) in the near-ultraviolet for the simultaneous detection of two key atmospheric trace species, HONO and NO2, is reported. For both compounds the absorption is measured between 360 and 380 nm with a compact cavity-enhanced spectrometer employing a high power light-emitting diode. Detection limits of ∼4 ppbv for HONO and ∼14 ppbv for NO2 are reported for a static gas cell setup using a 20 s acquisition time. Based on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 59 publications
1
129
0
Order By: Relevance
“…The technique has proved valuable for quantifying trace gases and aerosol extinction in chamber and field measurements (Venables et al, 2006;Dixneuf et al, 2009;Ball et al, 2010;Thalman and Volkamer, 2010;Washenfelder et al, 2008) and good agreement with other techniques has been demonstrated in recent intercomparisons of NO 2 and NO 3 measurements (Dorn et al, 2011;Fuchs et al, 2010). Most IBBCEAS measurements thus far have been at visible wavelengths, with the shortest wavelength measurements between 360 nm and 380 nm to quantify HONO and NO 2 (Gherman et al, 2008). To our knowledge, however, the technique has not been employed to record high quality reference spectra.…”
Section: Introductionmentioning
confidence: 85%
“…The technique has proved valuable for quantifying trace gases and aerosol extinction in chamber and field measurements (Venables et al, 2006;Dixneuf et al, 2009;Ball et al, 2010;Thalman and Volkamer, 2010;Washenfelder et al, 2008) and good agreement with other techniques has been demonstrated in recent intercomparisons of NO 2 and NO 3 measurements (Dorn et al, 2011;Fuchs et al, 2010). Most IBBCEAS measurements thus far have been at visible wavelengths, with the shortest wavelength measurements between 360 nm and 380 nm to quantify HONO and NO 2 (Gherman et al, 2008). To our knowledge, however, the technique has not been employed to record high quality reference spectra.…”
Section: Introductionmentioning
confidence: 85%
“…HONO and NO 2 outputs from the calibration source were measured using an incoherent broadband cavity enhanced absorption spectrometer (IB-BCEAS) (Washenfelder et al, 2009). IBBCEAS employs broadband light that is coupled into a high-finesse optical cavity to achieve a long effective pathlength, and has been used previously for measurements of HONO (Gherman et al, 2008;Langridge et al, 2009). The IBBCEAS instrument was modified for spectral measurements in the 357-372 nm region using a Nichia NCSU033A(T) UV LED and cavity mirrors (Advanced Thin Films) with manufacturer reported transmission of 0.0082% at their nominal center wavelength 362 nm.…”
Section: Ni-pt-cimsmentioning
confidence: 99%
“…When the optical cross section of the analyte species is known, the gas-phase concentration of the species may be calculated directly from the optical extinction. IBBCEAS has been used successfully to measure gas phase concentrations of NO 2 , NO 3 , CHOCHO, CH 3 COCHO, HONO, O 3 , I 2 , IO, and OIO (Ball et al, 2004;Venables et al, 2006;Washenfelder et al, 2008;Gherman et al, 2008;Vaughan et al, 2008;Thalman and Volkamer, 2010). Initial cavity measurements have reported aerosol extinction for ambient aerosol (Washenfelder et al, 2008;Varma et al, 2009;Thalman and Volkamer, 2010).…”
Section: Introductionmentioning
confidence: 99%